Replicated chromatin curtails 53BP1 recruitment in BRCA1-proficient and BRCA1-deficient cells - Michelena, Jone (Life Sci Alliance, 2021)
DNA double-strand breaks can be repaired by non-homologous end-joining or homologous recombination. Which pathway is used depends on the balance between the tumor suppressors 53BP1 and BRCA1 and on the availability of an undamaged template DNA for homology-directed repair. How cells switch from a 53BP1-dominated to a BRCA1-governed homologous recombination response as they progress through the cell cycle is incompletely understood. Here we reveal, using high-throughput microscopy and applying single cell normalization to control for increased genome size as cells replicate their DNA, that 53BP1 recruitment to damaged replicated chromatin is inefficient in both BRCA1-proficient and BRCA1-deficient cells. Our results substantiate a dual switch model from a 53BP1-dominated response in unreplicated chromatin to a BRCA1–BARD1–dominated response in replicated chromatin, in which replication-coupled dilution of 53BP1’s binding mark H4K20me2 functionally cooperates with BRCA1–BARD1–mediated suppression of 53BP1 binding. More generally, we suggest that appropriate normalization of single cell data, for example, to DNA content, provides additional layers of information, which can be critical for quantifying and interpreting cellular phenotypes.